Graphene-like coated steel tube via biased hollow cathode discharges. (October 2021) - Mariano, S.F.M.; Silva, C.; Medeiros, F.I.; Pillaca, E.J.D.M.; Ueda, M.
Abstract: The inner surface of a narrow steel tube was coated with a very thick graphene-based (Gr-like) layer by biasing the tube in a Plasma Immersion Ion Implantation and Deposition (PIII&D) process. The outcomes indicate that a multilayer graphene film was grown in well-aligned columnar structures, showing a typical cauliflower-like character. Local gas feeding was found not only to overcome the discharge breakdown in such a small tube, but it additionally leads to a completely different supply of carbon species. In this sense, Gr-like coated tubes could extend the applicability of PIII&D process to attend other engineered applications. Highlights: Gr-like films was deposited inside narrow metal tube. Crystallinity of the carbon films was enhanced by using local gas feeding. Heterogeneity of Gr-like films are explained in terms of acetylene gas pressure.